PEMERTAHANAN WARISAN BUDAYA BANGSA MELALUI SENI TRADISIONAL - Santi Susanti; Iwan Koswara (Jurnal Akrab Juara, 2018)
Culture existence, as one of the nation's identity, ought to be maintained in order not to be lost. Although the times keep changing, the original identity of the nation, should not be faded and diplaced by outside culture that comes slowly through information and communication technology development. Generations that lives in this millennial era is different than its predecessor generation, especially with the presence of digital media, which has become part of an integral part of their lives. This paper aims to reveal the efforts of traditional Sundanese dance artist in introducing Indonesian to the local community and abroad.. Using qualitative descriptive method with phenomenology approach, the results shows, the efforts to introduce traditional Sundanese Dance made through performances in a variety of arts events and missions abroad. Communication used is mostly symbolic communication that manifests in the form of dances as well as its supporting elements. Keywords: millennial, culture, identity, artistry, symbolic communication.